2009
DOI: 10.1889/1.3256968
|View full text |Cite
|
Sign up to set email alerts
|

66.2: Effects of Diluters on High Δn and Low Viscosity Negative Δε Liquid Crystals

Abstract: Lateral difluoro terphenyls exhibit a high birefringence, fairly low viscosity, and modest dielectric anisotropy, but their alignment in a VA cell is often deteriorated at elevated temperatures if their concentration goes high. We have studied the effects of six diluters for lowering the viscosity while stabilizing the VA alignment of the terphenyl host mixture at elevated temperatures. The pros and cons of each diluter are analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It is difficult for liquid crystal mixtures to achieve these excellent properties of high birefringence, large dielectric anisotropy, low viscosity, low melting point, and wide LC phase interval at the same time. Previous reports indicated that LC diluters are effective dopants to decrease the viscosity and melting point of the LC mixtures [8], [9] . For example, when LC diluter 5CC3 [10] was added to the LC mixture, the viscosity and melting point of the LC mixture was effectively decreased.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult for liquid crystal mixtures to achieve these excellent properties of high birefringence, large dielectric anisotropy, low viscosity, low melting point, and wide LC phase interval at the same time. Previous reports indicated that LC diluters are effective dopants to decrease the viscosity and melting point of the LC mixtures [8], [9] . For example, when LC diluter 5CC3 [10] was added to the LC mixture, the viscosity and melting point of the LC mixture was effectively decreased.…”
Section: Introductionmentioning
confidence: 99%